+0

# 1: Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

0
123
6
+547

1:  Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

2:  Consider the polynomials [f(x)=4x^3+3x^2+2x+1]and [g(x)=3-4x+5x^2-6x^3.] Find c such that the polynomial f(x)+cg(x) has degree 2.

3:  What is the coefficient of x^3 when 7x^4-3x^3 -3x^2-8x + 1 is multiplied by 8x^4+2x^3 - 7x^2 + 3x + 4 and the like terms are combined?

Thanks my dudes

AnonymousConfusedGuy  Nov 28, 2017
Sort:

#1
+82859
+1

1:  Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

Let us suppose that we have this form

P(x)  =   ax^3  + bx^2 +  cx  +  d       where d  =  47

So we have that

a  +    b +  c +   47  =  32    ⇒   a +  b +  c  =  -15

8a +  4b  + 2c + 47  = -13  ⇒  8a + 4b + 2c  =  -60

27a + 9b + 3c + 47  =  16  ⇒  27a + 9b + 3c  = -31

Multiply the first equation by -2 and add it to the second equation

Multiply the first equation by -3 and add it to the third equation

6a  +  2b  = -30   ⇒  3a + b =  - 15

24a + 6b =    14  ⇒ 12a + 3b  = 7

Multiply  the first equation by -3  and add it to the second

3a   = 52   ⇒    a  = 52/3

3(52/3) + b  =  -15  ⇒  52 + b  = -15   ⇒  b =   -67

(52/3) + (-67) + c  =  -15  ⇒  c  = -15 - 52/3 + 67   ⇒  c  =  104/3

So.... the sum of the coefficients is

52/3 - 67 + 104/3   =    -15

CPhill  Nov 28, 2017
#2
+547
0

Thanks a bunch, but...  My math program says that's wrong.  I couldn't find anything wrong with your calculation though?

AnonymousConfusedGuy  Nov 28, 2017
#5
+82859
0

Here is the graph : https://www.desmos.com/calculator/if4wjn6elr

All the specified points appear.....is it possible that the polynomial you want is of a different degree ???

CPhill  Nov 28, 2017
#6
+547
0

ah, I think it's looking for the coefficients of f, not the coefficients of 47, 32, -13, and 16, is it possible that would render a different answer?

AnonymousConfusedGuy  Nov 28, 2017
#3
+82859
+1

2:  Consider the polynomials [f(x)=4x^3+3x^2+2x+1]and [g(x)=3-4x+5x^2-6x^3.] Find c such that the polynomial f(x)+cg(x) has degree 2.

[4x^3+3x^2+2x+1] + c [ 3-4x+5x^2-6x^3]

[4x^3+3x^2+2x+1]  + c [ -6x^3 + 5x^2 - 4x + 3 ]

For a resulting polynomial to have degree 2,  we must have that

4  - 6c  =  0

4  =  6c

4/6  = c   =  2/3

So  we have the resulting polynomial

[4x^3+3x^2+2x+1]  + (2/3) [ -6x^3 + 5x^2 - 4x + 3 ]  =

(1/3) (19 x^2 - 2 x + 9)

CPhill  Nov 28, 2017
#4
+82859
+1

3:  What is the coefficient of x^3 when 7x^4-3x^3 -3x^2-8x + 1 is multiplied by 8x^4+2x^3 - 7x^2 + 3x + 4 and the like terms are combined?

[ 7x^4 - 3x^3 -3x^2 - 8x + 1 ] *  [ 8x^4 + 2x^3 - 7x^2 + 3x + 4 ]

The coefficient of the x^3 term will come from

(-3 * 4)   +  (-3 * 3) + (-8 * -7)  + (1 * 2)  =

-12      -   9          +    56    +   2   =

37

CPhill  Nov 28, 2017

### 26 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details